Numerical Simulation of Turbine Disk Cooling - YifeiZhu, XingYu , HuiShi, LeiZhao, HaizhouWang, YuhuaLu, FulinLi, HepingLiu, YaqingHou (Forest Chemicals Review)
Turbine disk is a very important component, and the cooling rate reflected in the heat treatment process has a great impact on its macro performance. Therefore, by means of numerical simulation, this paper makes an exploratory study on the cooling process of turbine disk in air and oil, and obtains the corresponding numerical calculation model which can be used to predict the heat treatment of turbine disk under different working conditions, At the same time, it is found that the cooling rate of the outer surface is much greater than that of the inner surface, and the cooling rate of oil is much greater than that of air.